2018
DOI: 10.2196/mhealth.9131
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Digital Health Use and Opinions of University Students: Field Survey Study

Abstract: BackgroundDuring university, students face some potentially serious health risks, and their lifestyle can have a direct effect on health and health behaviors later in life. Concurrently, university students are digital natives having easy access to the internet and new technologies. Digital health interventions offer promising new opportunities for health promotion, disease prevention, and care in this specific population. The description of the current use of and opinions on digital health among university st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
3
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 37 publications
7
62
3
11
Order By: Relevance
“…Our findings contribute to and extend previous research on women’s use of online health information sources in developed countries by focusing on more detail on how they access and use their sources in relation to medical consultations. Regardless of their age or education level, our participants were even more highly engaged in seeking health information online compared with the participants in studies based in the USA [ 10 , 11 , 22 24 ], the European Union, Germany [ 12 ] and France [ 13 ]. This finding may be partly due to the very high use of the internet and smartphones by Australians more generally compared with other populations [ 41 ].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our findings contribute to and extend previous research on women’s use of online health information sources in developed countries by focusing on more detail on how they access and use their sources in relation to medical consultations. Regardless of their age or education level, our participants were even more highly engaged in seeking health information online compared with the participants in studies based in the USA [ 10 , 11 , 22 24 ], the European Union, Germany [ 12 ] and France [ 13 ]. This finding may be partly due to the very high use of the internet and smartphones by Australians more generally compared with other populations [ 41 ].…”
Section: Discussionmentioning
confidence: 87%
“…Previous research has shown that women across a range of age groups engage more highly than men with online health information sources in countries such as the United States of America (USA) [ 10 , 11 ], Germany [ 12 ], France [ 13 ] and member states of the European Union [ 14 ]. The importance these sources play for pregnant women or those in the early years of motherhood has been the greatest focus of more detailed research on women’s engagements.…”
Section: Introductionmentioning
confidence: 99%
“…Percentage of patients with SLE reporting each medication within 30 days of PLM registration. PLM PatientsLikeMe, SLE systemic lupus erythematosus women are more likely than men to seek health information from the Internet[24][25][26]. Approximately 95% of the patients with SLE who reported a country of residence live in the United States.…”
mentioning
confidence: 99%
“…As today's leading medium, the internet offers great potential and wide reach for health promotion [1,2]. Especially among younger target groups, it is already established as a primary source of health information [3][4][5].…”
Section: Introductionmentioning
confidence: 99%